2002
DOI: 10.1073/pnas.062527199
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cells and somatic cells differ in mutation frequency and type

Abstract: Pluripotent embryonic stem (ES) cells have been used to produce genetically modified mice as experimental models of human genetic diseases. Increasingly, human ES cells are being considered for their potential in the treatment of injury and disease. Here we have shown that mutation in murine ES cells, heterozygous at the selectable Aprt locus, differs from that in embryonic somatic cells. The mutation frequency in ES cells is significantly lower than that in mouse embryonic fibroblasts, which is similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
221
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(234 citation statements)
references
References 36 publications
10
221
0
1
Order By: Relevance
“…This has indeed been found to be the case. 29 What regulates MMR in ES cells? As outlined in Figure 7b, MSH2 gene expression is governed by the transcription factor E2F1, 21 which is regulated by Rb.…”
Section: Discussionmentioning
confidence: 99%
“…This has indeed been found to be the case. 29 What regulates MMR in ES cells? As outlined in Figure 7b, MSH2 gene expression is governed by the transcription factor E2F1, 21 which is regulated by Rb.…”
Section: Discussionmentioning
confidence: 99%
“…The gain and loss of whole chromosomes and chromosome fragments are expected, while point mutations and mitotic recombination events are not. An analysis of loss-of-heterozygosity (LOH) mutations found that in mouse embryonic stem (ES) cells, the majority of LOH mutations were attributable to nondisjunction, whereas in mouse embryonic fibroblasts, LOH owing to nondisjunction was not observed (Cervantes et al, 2002). The LOH events in ES cells are likely to arise from the decatenation checkpoint deficiency in those cells.…”
Section: Checkpoint Deficiency and Chromosome Instabilitymentioning
confidence: 99%
“…A similar system in mice, based on a heterozygous mutation in the (autosomal) Aprt gene, also allows mutation analysis in vivo by screening for loss of the remaining wild-type allele in somatic cells[47]. These assays, however, can only be performed on cells that can actively proliferate in culture.…”
Section: Introductionmentioning
confidence: 99%